(untitled) (Applied Biological Research, 2012)
Bovine viral diarrhea (BVD) infection causing great reproductive and productive losses is an immunosuppression seen in all age groups of ruminants world-wide. In present study out of 78 peripheral blood leucocyte (PBLs) samples 4 samples were positive for BVDV antigen by pestivirus antigen-capture ELISA, while none of the faecal samples was positive for BVDV antigen by AGID and RT-PCR. The use of RT-PCR on all PBLs samples was restricted to the above 4 positive samples which yielded a 288 bp amplicon, while rest were found negative. The BVDV positive samples were confirmed by restriction endonuclease analysis. The study revealed the presence of BVDV in Mathura region of Uttar Pradesh.